Soil phosphatases: factors affecting enzyme activity in Arctic tussock tundra and Virginia mineral soils - Herbein, Sue Bortz (Virginia Polytechnic Institute and State University, 1981)
The effect of pH, temperature, substrate concentration, and orthophosphate on abiontic phosphomonoesterase activity was examined in disturbed and undisturbed Arctic soils with variable moisture content and in Virginia forest, grassland and agricultural soils. Distribution of acid and alkaline phosphatases was related to soil pH. The pH optimum for enzyme activity was near 5.5 in all soils except agricultural soil where it was 11. The pH of all soils except agricultural soil was between 4.7 and 6.6. At pH 5.5 enzyme activity was 10 to 20 fold greater in O e - O i horizon Arctic soils than in Ap horizon Virginia soils. Undisturbed Arctic soils had 30-40% greater activity than disturbed soils. Phosphomonoesterase activity in each soil was 10 fold greater than either phosphodiesterase or phosphotriesterase activity in the same soil. Three hundred to 700 µg p-nitrophenol ·g¹ h¹ were released by Arctic soils incubated at 0°C; levels increased as temperature increased. K m app (v: v/S regression analysis) ranged from 1.57 to 2.91 mM (Arctic) and 2.11 to 3.23 mM (Virginia). V max expressed as µmoles·g¹ h¹, ranged from 17.6 to 23.2 (Arctic) and 0.52 to 3.66 (Virginia). Orthophosphate inhibition of p-nitrophenyl phosphatase activities was competitive or mixed in Arctic soils and competitive in Virginia soils. K i ranged from 3.4 to 11.7 mM (Arctic) and 4.12 to 15.6 mM (Virginia). Data suggests that the potential for phosphatase catalyzed phosphate hydrolysis is greatest in the organic Arctic soils (gram dry weight basis) and activity in those soils is influenced by disturbance and moisture. Master of Science